Intergenerational transmission of physical discipline: effects of physical discipline on externalising and internalising behaviours in Singapore - Chow, Tracy Si Ting (Nanyang Technological University, 2023)
The use of physical discipline remains prevalent in Singapore and is widely accepted. Past studies have found physical discipline to be linked with adverse outcomes and many regions have established laws prohibiting its use. Yet, it is not prohibited in any setting for Singapore. Currently, no research in Singapore examines the effects of intergenerational transmission of physical discipline and its impact on externalising and internalising behaviours in early adulthood. Using a sample of young adults and their parents, Study 1 aims to conduct a descriptive study of the intergenerational transmission of physical discipline experience in Singapore. Study 2 aims to investigate if intergenerational transmission of maternal and paternal physical discipline experiences predicts young adults’ externalising and internalising behaviours. Study 1 found that physical discipline is still normalised within families. Furthermore, a greater number of cycle breakers was found among parents compared to cycle initiators, which may indicate that more parents are becoming aware of the negative consequences of physical discipline. Study 2 found that more frequent young adults’ childhood physical discipline is predictive of young adults’ greater externalising and internalising behaviours, but parents' childhood physical discipline was not. Moreover, both maternal and paternal use of physical discipline resulted in negative consequences for young adults. Findings emphasises the importance of implementing interventions to shift cultural and societal norms surrounding physical discipline to facilitate changes in behaviours towards effective non-physical disciplinary strategies for future generations in Singapore.